SERANGAN NEMATODA SISTA KUNING (Globodera rostochiensis) PADA TANAMAN KENTANG DI KABUPATEN BANJARNEGARA ATTACKS OF GOLDEN CYST NEMATODE (Globodera rostochiensis) ON POTATO AT BANJARNEGERA REGENCY - Manan, Abdul (Pembangunan Pedesaan, 2005)
Golden cyst nematode (Globodera rostochiensis) is the main nematode on potato. In recent years, the nematode has been reported at several potato production centers in Indonesia. This research aimed at knowing distribution of the nematode attacks on potato at Banjarnegara Regency and factors supporting its attack. Survey was conducted by using purposive random sampling as a sampling method. Results of the research showed that G. rostochiensis was found at three districts, i.e., Batur, Pejawaran, and Wanayasa, but its populations were still -1 concentrated at Karangtengah Village, Batur District, namely 37.28 cysts 200 ml -1 soil and 10.76 cysts plant . The nematode presumably entered Banjarnegara Regency through imported potato seedlings, available potato host, and appropriate environment temperature supporting the nematode growth and development.